A bacia inferior do rio Real : uma análise socioambiental - Costa, Boni Guimarães (2011)
The watershed is defined as all land drained by a main river and its tributaries, is taken as a unit of analysis of the surface, where it is possible to study the interrelationships between landscape elements, in this sense, the area study, the lower basin of the Rio Real, is composed of municipalities of Bahia and Rio Real Jandaíra and the municipalities in Sergipe Cristinápolis, Indiaroba, Itabaianinha, and take the Geru Umbaúba. It is endowed with unique environmental features such as coastal plain formed by salt marshes, mangroves that were originated by the superposition of beach ridges and dune fields. Given that this work is to analyze the social and environmental conditions of the Lower Basin of the Rio Real as well as providing grants for the planning and environmental management. The theoretical and methodological studies was based on Bertrand that offered subsidies for integrated studies. Thus, to achieve the objectives were achieved bibliographic, cartographic, documentary and field, where he found the performance of various social actors in shaping the landscape, like the economic activities: citrus, cocoicultura, cattle, shrimp farming and tourism, with especially the city of Jandaíra / BA, which according to the beauty of the landscape of Mangue Seco Village attracts many domestic and international tourists, even in this town on the beach of Costa Azul is no prospect of construction of resorts, which may contribute to increased tourist flow. In addition, we sought from the relevant units (Coastal Plains, Coastal Plains and the Rio Real trays), to analyze geosystems of geoenvironmental conditions, economic activities and population aspects of its tourism potential. It is responsible for the planning and management, promote sustainable development and enhancing the beneficial effects consistent with the principles of equality, social justice and environmental sustainability.